Sportivnaya deyatel'nost' i sposobnosti - Salnikov, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The sport activity is one of the areas, where the abilities play the determining role in the achievements of a human being. However, there are many disputable and debatable moments with not only general theoretical character, but also with itsreference to the specificity of concrete activity. It is not possible to analyze that variety of definitions of the concept of "ability", which meets in the scientific literature obviously. The success of sports activity is determined not only by the maximal realization of available abilities, strong-willed displays, motivational bases, knowledge and skills should promote this to the full. The primary factor promoting the realization of motor abilities, that is conformity of it to the chosen kind of an activity. The determining in this case are the properties of a nervous system acting as the features of motor abilities.